Česko-německé kontakty ve světle antroponymie českých zemí - Pleskalová, Jana (Linguistica (Ljubljana), 2015)
A diachronic analysis of Czech-German relationships in relation to the anthroponymy of the Czech lands has revealed that the most significant effect of the contact can be seen in the domain of personal names. First, a common inventory of Christian names formed as a result of the close contact of the Czech-speaking population with the newly arrived German-speaking population and under the unifying influence of the Roman Catholic church. Important parts of the inventory were formed by names relating to the church (e.g. Jan/Johannes/Johann, Nicolaus/Mikuláš, Petr/Peter/Petrus, Margaretha/Markéta, Katharina/Kateřina) and by German names (Henricus/Heinrich, Albertus/Albert/Albrecht, Ulricus/Ulrich), used more frequently by the Czech-speaking inhabitants only until the end of the 18th century. On the other hand, the most significant Czech names related to the church were - although to a small extent - accepted within the German community (Václav/Wenzel, Ludmila, Vojtěch). Second, a more sophisticated way of identifying a person by using a two-element name (a Christian name and complementary anthroponym, later on a hereditary surname - Johannes Schwarz), preferred by the German speaking inhabitants of the Czech lands already since the 14th century, influenced and also speeded up the introduction of the two-name system in Czech community (Jan Kohout), although only in the case of male representatives of families. The close Czech-German contacts ended after World War II in 1945 by the expulsion of Germans from the Czechoslovakia. Since then, names of German origin occur in the Czech Republic only scarcely, mostly as a family tradition (a father named Karel, a son named Karel, similarly Jindřich, Oldřich etc.).
Keywords: allemand; anthroponymes; antroponimi; češčina; German; jeziki v stiku; langues en contact; nemščina; osebna imena